Mathematics, the Common Core, and RTI : an Integrated Approach to Teaching in Today's Classrooms. - Burton, Dolores T. (SAGE Publications, 2013)
Don't let the revolution in math education pass your teachers by! Individually, the Common Core and RTI are formidable enough. Together, they create a "perfect storm" of challenges, with most teachers left wondering where to turn first. Finally, here's a resource that distills the central elements of the Common Core and RTI into a single, manageable instructional strategy for serving all students. It provides: Real-world scenarios Classroom-ready work samples Content-area applications Recommended online resources Guidance on special-needs students, behavioral issues, ELLs, and parent invol